Protein as the building blocks of life / Rania Farzana Azmi ... [et al.] - Azmi, Rania Farzana; Azami, Azleen Nurkarmilya; Mohamad Salin, Nur Shafinaz; Md Saad, Wan Mazlina (2021)
Protein is not limited to being a source of food but also provides other benefits such as maintaining body weight, key nutrients for bone health and reduces disease risks including type 2 diabetes and neurodegenerative diseases such as Alzheimer's, Huntington's and Parkinson's disease. With those benefits, it is essential to consume protein for optimal growth and development in an individual. Proteins are made up of amino acids and can be classified into four major structures. Primary structure is a linear sequence of amino acids in a polypeptide chain with an example of insulin productions. Next, protein secondary structure includes alpha-helix or folded into beta-pleated sheets due to their crucial structure role in most globular and fibrous proteins. The formation of alpha-chain and betapleated sheets is due to hydrogen bonding between carbonyl and amino groups in the peptide backbone. Moving on to the production of essential biological compounds such as enzymes, hormones, antibodies, and plasma protein which are the examples of tertiary structure that either has folded helix or formed pleated sheet into a 3-D polypeptide shape. Factors influencing the R chain in tertiary structures include ionic interactions, hydrogen bonds, Van der Waals depressive forces, and sulfur bridges mainly caused by amino acid group interactions. Quaternary structure is the combination of two or more tertiary structure polypeptide chains that form one large and complex protein molecule. For instance, the synthesis of haemoglobin where the organisation of protein is in multiple subunits. Evidence from repairing and building new cells in providing one's body framework proves that proteins must be included in our daily diet to maintain a healthy lifestyle.